Fanconi Anemia: Challenges in Diagnosis and Management—A Case Series Report - Aziz Eghbali; Seyed Mehrab Safdari; Maedeh Yousefi Roozbahani; Khatereh Tavajohi; Soudabeh Hosseini (Clinical Case Reports)
ABSTRACT Fanconi anemia (FA) is a rare inherited disorder characterized by congenital abnormalities, progressive bone marrow failure, and a predisposition to malignancies. Detecting FA can be challenging, as it involves identifying increased chromosomal sensitivity to DNA cross‐linking agents and detecting causative genetic variants via genome sequencing. We report two cases of siblings with FA, both confirmed to have the FANCD2 variant through whole‐exome sequencing (WES). The first patient presented with epistaxis, petechiae, ecchymosis, and lower limb edema. The second patient exhibited epistaxis, diabetes, developmental delay, and physical abnormalities. Interestingly, both patients had negative results on the initial chromosomal breakage test with mitomycin C, a commonly used diagnostic tool for FA. However, further investigation with WES revealed the presence of the FANCD2 variant, confirming the FA diagnosis. This case report highlights the challenges in diagnosing FA, particularly when initial screening tests yield negative results. Molecular genetic testing, such as WES, can provide a definitive diagnosis and guide appropriate management strategies. Early and accurate diagnosis is crucial for improving outcomes in individuals with this potentially fatal illness, as promising advancements in treatments such as hematopoietic stem cell transplantation and gene therapy offer hope for addressing FA.